Molecular Identification of Organisms from Bread Mold - Donatus, Glory Mendie; Chuku, Sobomate; Jude, Keayiabarido; Uzoma, Miracle; Bakpo, Emmanuel; Numbere, Aroloye (Food and Drug Safety, 2026)
The study focused on the molecular identification of organisms associated with bread mold with the aim of isolating, characterizing, and accurately identifying fungal contaminants responsible for bread spoilage. One gram (1 g) of a contaminated bread sample was serially diluted and cultured on Potato Dextrose Agar (PDA). The pure isolates were coded as GBMF1, GMBF2, GBMF3, and GBMF4, and incubated for another three days. Pearson correlation was used to determine if there is a difference in the genetic distance between the isolates at p = 0.05. After incubation, the fungal structures were observed under the ×40 objective lens for microscopic characterization. Morphological and microscopic characterization suggested that the isolates belonged to the genera Aspergillus, Cladosporium, Penicillium, and Fusarium. Genomic deoxyribonucleic acid (DNA) was successfully extracted from two of the isolates (GBMF1 and GBMF4) with purity ratios ranging from 1.70 to 1.80 and concentrations between 24 and 31 ng/μL. Polymerase Chain Reaction (PCR) amplification of the internal transcribed spacer (ITS) region produced clear bands of approximately 600 bp, confirming the presence of fungal DNA. Sequencing and Basic Local Alignment Search Tool for nucleotides (BLASTn) analysis revealed that isolate GBMF1 had 100% similarity with Aspergillus niger, while isolate GBMF4 showed 75–88% similarity with Fusarium equiseti and related taxa. The findings demonstrate that combining morphological and molecular techniques provides accurate and reliable identification of fungi in spoiled bread. Practically, the study emphasizes the need for strict hygiene in bread production, proper storage, and routine molecular surveillance to ensure food safety and reduce public health risks associated with mycotoxigenic fungi.